Increasing Stability and Activity of Core–Shell Catalysts by Preferential Segregation of Oxide on Edges and Vertexes: Oxygen Reduction on Ti–Au@Pt/C - Hu, Jue; Wu, Lijun; Kuttiyiel, Kurian A; Goodman, Kenneth R; Zhang, Chengxu; Zhu, Yimei; Vukmirovic, Miomir B; White, Michael G; Sasaki, Kotaro; Adzic, Radoslav R (Journal of the American Chemical Society, 2016)
We describe a new class of core–shell nanoparticle catalysts having edges and vertexes covered by refractory metal oxide that preferentially segregates onto these catalyst sites. The monolayer shell is deposited on the oxide-free core atoms. The oxide on edges and vertexes induces high catalyst stability and activity. The catalyst and synthesis are exemplified by fabrication of Au nanoparticles doped by Ti atoms that segregate as oxide onto low-coordination sites of edges and vertexes. Pt monolayer shell deposited on Au sites has the mass and specific activities for the oxygen reduction reaction about 13 and 5 times higher than those of commercial Pt/C catalysts. The durability tests show no activity loss after 10 000 potential cycles from 0.6 to 1.0 V. The superior activity and durability of the Ti–Au@Pt catalyst originate from protective titanium oxide located at the most dissolution-prone edge and vertex sites and Au-supported active and stable Pt shell.